GAMBARAN TINGKAT PRODUKTIVITAS KERJA BERDASARKAN LINGKUNGAN DAN MOTIVASI KERJA PETUGAS ASSEMBLING RUMAH SAKIT UMUM PUSAT Dr. HASAN SADIKIN TAHUN 2020 - Try Ganjar Wati; Sustin Farlinda; Efri Tri Ardianto (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2021)
Based on the results of a preliminary study conducted at Hasan Sadikin Hospital, it is known that fromFebruary to March 2020 the achievement of the 20 files per day assembling task target has not been fullyachieved. 7 out of 9 assembling officers work 7 to 15 files and there was an inconsistency of the additionalform's location that assessed by each officer. This resulted in narrow space and files that were stacked toolong causing the medical record file to be damaged and the location of the additional forms to be different.This study aims to describe the level of work productivity based on the environment and the work motivationof assembling officers Dr. Hasan Sadikin 2020. This type of research uses quantitative by observing anddistributing questionnaires to respondents. The results obtained are that the assembling officer at RSUP Dr.Hasan Sadikin who has a higher level of productivity are officers with male sex, age categories 35-49 years,length of work for more than 10 years, last education diploma IV / S1, and with marital status.